Perceptions of HIV Self-Management Roles and Challenges in Adolescents, Caregivers, and Health Care Providers. (July 2019) - Mutumba, Massy; Musiime, Victor; Mugerwa, Henry; Nakyambadde, Hellen; Gautam, Anudeeta; Matama, Christine; Stephenson, Rob
Abstract : Abstract: Self-management of HIV is a desirable goal for the millions of adolescent persons living with HIV (PLWH). Adolescent PLWH continue to experience poor HIV care outcomes, primarily due to poor rates of medication adherence and retention in care, highlighting a need to develop adolescent self-management skills. The aim of our study was to examine adolescent, caregiver, and health care provider perceptions of adolescent PLWH self-management roles, barriers, and facilitators. Swendeman et al.'s self-management framework for chronic diseases guided the analyses. Participant narratives highlighted perceptions of their responsibilities and related challenges with regard to self-management of HIV by adolescents. Our findings highlighted the complexity of HIV self-management for adolescents and underscored the need for multifaceted programs to strengthen adolescent–caregiver–health care provider partnerships in order to improve adolescent PLWH health and wellbeing.